2004
DOI: 10.1038/sj.ejcn.1602020
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Lactobacillus acidophilus and Bifidobacterium longum do not alter urinary equol excretion and plasma reproductive hormones in premenopausal women

Abstract: Objective: To confirm the results of an earlier study showing premenopausal equol excretors to have hormone profiles associated with reduced breast cancer risk, and to investigate whether equol excretion status and plasma hormone concentrations can be influenced by consumption of probiotics. Design: A randomized, single-blinded, placebo-controlled, parallel-arm trial. Subjects: In all, 34 of the initially enrolled 37 subjects completed all requirements. Intervention: All subjects were followed for two full men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 37 publications
3
36
1
1
Order By: Relevance
“…The proportion of equol-and ODMA-producers in our study was similar to that reported elsewhere in predominantly Caucasian populations [16,19,35,36]. Similarly, mean percent breast density among women in this study was comparable with that reported for premenopausal women in other studies [37][38][39], although some have reported slightly higher levels of density [40,41]; this could be due to the fact that we recruited women stratified by BIRADS density score to include premenopausal women with low, as well as high, densities.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The proportion of equol-and ODMA-producers in our study was similar to that reported elsewhere in predominantly Caucasian populations [16,19,35,36]. Similarly, mean percent breast density among women in this study was comparable with that reported for premenopausal women in other studies [37][38][39], although some have reported slightly higher levels of density [40,41]; this could be due to the fact that we recruited women stratified by BIRADS density score to include premenopausal women with low, as well as high, densities.…”
Section: Discussionsupporting
confidence: 87%
“…For logistical reasons, we were unable to measure breast density, hormone concentrations, and daidzein-metabolizing phenotypes on the same day. This is unlikely to have affected our findings given that the daidzein-metabolizing phenotypes are relatively stable within individuals over time [52,53] and that it does not seem possible to change the phenotypes with dietary intervention [35,[54][55][56]. Furthermore, we included only premenopausal women who were not currently using exogenous hormones and had not used them at the time of, or in the 6 months prior to, their mammogram.…”
Section: Discussionmentioning
confidence: 86%
“…In premenopausal women, who are equol producers, the reproductive hormone pattern is consistent with lower risk of breast cancer (independent of isoflavone dose intake) [98]. However, other studies did not replicate these findings [99,100].…”
Section: Breast Cancermentioning
confidence: 93%
“…However, the low soy dose provided 10 mg of isoflavones per day, which is higher than mean intakes in Western populations [39,40], and it is possible that low levels of equol may be capable of eliciting biological responses. In subsequent, relatively small, studies in pre- [30] and postmenopausal [17] women, there were no significant differences between producers and non-producers of equol and ODMA (postmenopausal women only), in circulating concentrations of estrogens or androgens in the absence of prolonged soy consumption. In our study we did not observe any statistically significant differences between producers and nonproducers of ODMA in circulating concentrations of estrogens, androgens, or SHBG.…”
Section: Discussionmentioning
confidence: 86%
“…This suggested a potential role for the equol-producer phenotype that was independent of soy or isoflavone dose. However, this was not shown in a subsequent study in premenopausal women [30]. Few studies have examined the potential health effects associated with the production of ODMA.…”
Section: Introductionmentioning
confidence: 91%